Chemical Synthesis of the 12 kDa Human Myokine Irisin by α‐Ketoacid‐Hydroxylamine (KAHA) Ligation. Issue 12 (27th October 2016) - Wucherpfennig, Thomas G.; Müller, Sebastian; Wolfrum, Christian; Bode, Jeffrey W.
Abstract : Irisin is a recently discovered protein hormone with a conserved sequence among vertebrates and with putative functions in the regulation of adipose tissue and bone metabolism. We report the first chemical synthesis using two sequential ketoacid‐hydroxylamine (KAHA) ligations to give milligram quantities of unlabeled and fluorescence‐labeled irisin protein. The synthetic proteins were utilized in cell binding assays, which indicated the expected binding characteristics to stromal cells of white adipose tissue. These studies strongly imply the presence of a specific irisin receptor and provide a path to its identification with synthetic irisin. Abstract :